2016
DOI: 10.1177/2150135116675844
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Visualization of Human Cardiac Conduction Tissue in Whole Heart Specimens by High-Resolution Phase-Contrast CT Imaging Using Synchrotron Radiation

Abstract: This is the first demonstration that visualization of the AV conduction axis within human whole heart specimens is feasible with PCCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…Propagation-based X-PCI (PB-X-PCI) has been previously proposed for the assessment of detailed cardiac structure both in excised non-beating rodent 18–20 and post-mortem human hearts 21–23 . In addition, fetal, neonatal and infant hearts have been assessed using synchrotron grating interferometry (GI) 24,25 , an alternative quantitative phase contrast imaging method. However, this technique would result in more challenging multiscale acquisitions with higher instrumentation requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Propagation-based X-PCI (PB-X-PCI) has been previously proposed for the assessment of detailed cardiac structure both in excised non-beating rodent 18–20 and post-mortem human hearts 21–23 . In addition, fetal, neonatal and infant hearts have been assessed using synchrotron grating interferometry (GI) 24,25 , an alternative quantitative phase contrast imaging method. However, this technique would result in more challenging multiscale acquisitions with higher instrumentation requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications have leveraged the 10-mm spatial resolution and high soft-tissue contrast. These have included visualizing myocardial fiber orientation (98)(99)(100), identifying the cardiac conduction system (101), visualizing microscopic vascular damage (102), and performing cardiac material decomposition (103). These experimental techniques may enable noninvasive high-resolution imaging of high-risk plaque and identification of subtle myocardial abnormalities in patients with cardiac disease.…”
Section: Development Of Phase-contrast Ct Toward Clinical Cardiovascumentioning
confidence: 99%
“…We have now shown that, when using phase-contrast computed tomography, it is possible to demonstrate the precise location of the conduction axis relative to its surroundings without destroying or altering the properties of autopsied human heart specimens. 9,10 The aim of this study is, therefore, to visualize and measure the location of the axis in the setting of atrioventricular septal defect with common atrioventricular junction using this technique.…”
Section: Introductionmentioning
confidence: 99%